Common Market—A step towards unification - Friedrich Wehner (Intereconomics, 1967)
The focus of the Conference of the Organisation of American States held in April 1967 at Punta del Este was the efforts to achieve the economic integration of South America. The most important item in the “Declaration by the American Presidents” at Punta del Este is the projected creation of a Common Market for the whole of Latin America. The Latin American Free Trade Association (ALALC) and the Central American Common Market (MCC) are to be the foundation for economic integration over a vast area. The statement put out by the Punta del Este Conference is, however, only the first step along the road towards the economic consolidation of South America. It is now up to the Latin American countries to bring true these oft-repeated protestations of Latin American solidarity. All the Latin American countries will have to co-operate purposefully to tackle the tasks ahead of them and they will need the support of the larger industrial nations, particularly the United States. Nothing less than economic collaboration between the countries of the american sub-continent, forgetting all national rivalries, would enable Simón Bolivar's dream of a strong and united Latin America to become a practicable reality. The following contribution discusses the ways and means of Latin American integration, the results achieved hitherio and the prospects for a comprehensive unification of South America—including political unification.
Keywords: 330; Latin American Integration